Hubungan Antara Lama Menjalani Hemodialisa Dengan Kualitas Hidup Pasien Gagal Ginjal Kronik Di Ruang Hemodialisa Di Salah Satu RSUD Di Batam - Siska Natalia; Fitriany Suangga; Wulan Pramadhani; Isnaini Isnaini (An-Najat, 2023)
Chronic kidney failure is one of the most common diseases suffered by patients with palliative conditions. Health conditions that decline and require routine dialysis can affect the biopsychosociospiritual of patients, The purpose of this study was to determine the relationship between the duration of hemodialysis and the quality of life of patients with chronic kidney failure. The research design used quantitative correlational, questionnaire using KDQOL. Data analysis using the Kolmogrov-Smirnov bivariate test. The results showed a sufficient quality of life as many as 13 respondents (43.3%), respondents who had a good quality of life as many as 7 respondents (23.3%) and respondents with a quality of life of less than 10 respondents (33.3%). With a p value of 0.033 (P<0.05), these results showed a significant relationship between the length of hemodialysis and the quality of life of patients with chronic renal failure. The recommendation for future research is an in-depth exploration of patients using qualitative methods to be able to explore the quality of life of patients with chronic kidney failure.